A Comparative Study on the Efficacy of Four Types of Circumcision for Elderly Males with Redundant Prepuce - Mu, Jiagui; Fan, Li; Liu, Duo; Zhu, Dongsheng (Urology Journal, 2020)
Purpose: Circumcision is a common human urologic surgery performed in males with redundant prepuce to prevent the transmission and reduce the risk of urologic diseases. However, the optimal circumcision method for elderly men remains to be determined. Herein, the current study was conducted to characterize the efficacy of four different kinds of circumcision for elderly males with redundant prepuce. Methods: This retrospective study included 132 elderly males diagnosed with redundant prepuce who underwent circumcision at the outpatient department. Among them, 38 cases were subjected to traditional surgery (Group A), 23 cases to sleeve circumcision (Group B), and 42 cases to Shang Ring circumcision (Group C) and 29 cases to suturing device circumcision (Group D). Subsequently, the operation time, loss of blood, postoperative pain, complications, wound healing, and the satisfaction were respectively compared and analyzed. Results: The operation time of these 4 groups was calculated to be 27.3 ± 2.39 min, 30.4 ± 2.23 min, 6.3 ± 1.33 min, 7.6 ± 1.29 min, in Group A, Group B, Group C, Group D, respectively (P < 0.05). Besides, the loss of blood was 15.6 ± 2.84 mL, 11.8 ± 1.73 mL, 1.3 ± 0.44 mL, 3.7 ± 1.41 mL, respectively (P < 0.05). The elderly males who underwent Shang Ring circumcision exhibited the highest postoperative pain score, the longest pain duration, the longest healing time, the lowest recovery satisfaction rate and the highest operation experience satisfaction rate (P < 0.05). Conclusion: Taken together, all four types of male circumcision present with advantages and drawbacks. The traditional male circumcision and sleeve circumcision led to longer operation time and more bleeding, but no additional medical equipment was needed. Meanwhile, the Shang Ring circumcision caused the shortest operation time and the least bleeding, accompanied by the longest pain duration and recovery time. Therefore, the application of sleeve circumcision or a suturing device was recommended for elderly males suffering from redundant prepuce.